2021
DOI: 10.7554/elife.65773
|View full text |Cite
|
Sign up to set email alerts
|

HPF1 and nucleosomes mediate a dramatic switch in activity of PARP1 from polymerase to hydrolase

Abstract: Poly(ADP-ribose) polymerase 1 (PARP1) is an important player in the response to DNA damage. Recently, histone PARylation factor (HPF1) was shown to be a critical modulator of the activity of PARP1 by facilitating PARylation of histones and redirecting the target amino acid specificity from acidic to serine residues. Here we investigate the mechanism and specific consequences of HPF1-mediated PARylation using nucleosomes as both activators and substrates for PARP1. HPF1 provides that catalytic base Glu284 to su… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
38
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 52 publications
(45 citation statements)
references
References 74 publications
(101 reference statements)
7
38
0
Order By: Relevance
“…In accordance, using novel HPLC assays quantifying ADP-ribose, NAD + and nicotinamide, Rudolph et al. could recently show that the presence of HPF1 leads to the release of ADP-ribose, resulting in distinctly shorter PAR chains ( 60 ). Additionally, activation of PARP1 by the Y-box-binding protein 1 (YB-1) has been shown to increase total protein PARylation but at the same time decrease the length of PAR ( 108 ).…”
Section: Determinants Of Par Structural Heterogeneitymentioning
confidence: 80%
“…In accordance, using novel HPLC assays quantifying ADP-ribose, NAD + and nicotinamide, Rudolph et al. could recently show that the presence of HPF1 leads to the release of ADP-ribose, resulting in distinctly shorter PAR chains ( 60 ). Additionally, activation of PARP1 by the Y-box-binding protein 1 (YB-1) has been shown to increase total protein PARylation but at the same time decrease the length of PAR ( 108 ).…”
Section: Determinants Of Par Structural Heterogeneitymentioning
confidence: 80%
“…As an example, the important recent discovery surrounding PARP-1 molecular functions have revealed that it can switch between PARylating and PAR hydrolysis activity via a HPF-1dependent mechanism (Rudolph et al, 2021). Importantly, both of these processes readily consume NAD + , exemplifying potential importance for our conception of PARPs as pure NAD + consumers and indicates a more sophisticated model of PARylation and its biological roles.…”
Section: Discussionmentioning
confidence: 99%
“…Parthanatos, a cell death pathway dependent upon PAR chain formation, works independent of caspase activity and has been attributed to PARPmediated NAD + depletion (reviewed in David et al, 2009 andRobinson et al, 2019). Recently, the histone PARylation factor 1 (HPF-1) has been identified as an integral modulator of PARP-1 PARylating activity as part of the DNA damage response (Gibbs-Seymour et al, 2016;Suskiewicz et al, 2020;Rudolph et al, 2021). Such work has provided novel insights into the factors that modulate rates of NAD + degradation by PARP-1 and has implications for the future development of PARP inhibition as a clinical strategy.…”
Section: Parpsmentioning
confidence: 99%
“…Moreover, exciting recent work indicates that factors such as HPF1 can switch the in vitro activity of PARP1 from a polymerase to hydrolase. 36 One impact of this is that the average length of the ADPr oligomer is severely reduced, potentially down to mono-ADP-ribosylation in combination with PARG activity. 37 Based on our current and previous data, 5 we can propose that ALC1 activity would be exquisitely sensitive to all cellular events that result in dynamic changes to the balance of mono-, di-, oligo-and poly-ADPr on chromatin.…”
Section: Discussionmentioning
confidence: 99%